Impact of the economic crisis on the activity of a clinical research ethics committee - Paula Arcenillas; Nuria Giménez; Pablo March López; S. Redondo Capafons; Laura Soriano; Ramon Pla; Salvador Quintana (Farmacia Hospitalaria)
Purpose: Analyze the impact of economic and social crisis in volume and funding of clinical trials (CT) and observational studies (ES) from the activity of an Research Ethics Committee (REC). Method: REC memories 2003-2012 were reviewed. Financing of evaluated projects, CT and OS were analyzed classifying them into four groups: 1) promoted by pharmaceutical industry, 2) by scientific societies with industry support, 3) by scientific societies with government support and 4) unfunding.Two periods were compared: pre-crisis (2003-2007) and crisis (2008-2012). Results: During 10 studied years, 744 protocols were evaluated: a 71% of group 1, a 9% of group 2, a 3% of group 3 and a 17% was no funding. Regarding OS, 40%, 5,4%, 8,6% and 46% were the groups 1, 2, 3 and 4 respectively. Analyzing crisis versus pre-crisis period, statistically significant differences were observed in the decreasing of number of CT phase 2 and 3 and in the rising EO. Comparing crisis related to the pre-crisis period, the Group 4 increased statistically significantly. Conclusions: Evolution of total number of studies evaluated by REC tends to be maintained and even increased over time. REC maintains its activity and even increased at the expense of financing and unfunded OS.